2007
DOI: 10.1093/jxb/erm003
|View full text |Cite
|
Sign up to set email alerts
|

High temperature stress and spikelet fertility in rice (Oryza sativa L.)

Abstract: In future climates, greater heat tolerance at anthesis will be required in rice. The effect of high temperature at anthesis on spikelet fertility was studied on IR64 (lowland indica) and Azucena (upland japonica) at 29.6 degrees C (control), 33.7 degrees C, and 36.2 degrees C tissue temperatures. The objectives of the study were to: (i) determine the effect of temperature on flowering pattern; (ii) examine the effect of time of day of spikelet anthesis relative to a high temperature episode on spikelet fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
488
2
13

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 627 publications
(523 citation statements)
references
References 15 publications
20
488
2
13
Order By: Relevance
“…A drastic reduction in seed set at high temperatures has also been observed in rice. Jagadish et al (2007) observed that exposure of rice at peak anthesis to 34°C for 1 h at about 1100 h caused sterility, while exposure of rice spikelets to [35°C for 5 days at anthesis induced complete sterility (Satake and Yoshida 1978). In rice, genotypic variation in spikelet sterility at high temperature has been observed in a number of studies (Satake and Yoshida 1978;Matsui et al 2001;Prasad et al 2006), attributed to differences in the temperature threshold required to induce sterility (Nakagawa et al 2002).…”
Section: Impact Of Climate Change On Cropping Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…A drastic reduction in seed set at high temperatures has also been observed in rice. Jagadish et al (2007) observed that exposure of rice at peak anthesis to 34°C for 1 h at about 1100 h caused sterility, while exposure of rice spikelets to [35°C for 5 days at anthesis induced complete sterility (Satake and Yoshida 1978). In rice, genotypic variation in spikelet sterility at high temperature has been observed in a number of studies (Satake and Yoshida 1978;Matsui et al 2001;Prasad et al 2006), attributed to differences in the temperature threshold required to induce sterility (Nakagawa et al 2002).…”
Section: Impact Of Climate Change On Cropping Systemsmentioning
confidence: 99%
“…In peanuts it was shown that genotypic variation in the optimum temperature for pollen germination varied from 25.5 to 35.0°C and for pollen tube growth from 30.5 to 36.8°C (Kakani et al 2002) suggesting that selection for high-temperature tolerance is feasible. Based on the observation that the floret is sensitive to high temperature at peak anthesis (Jagadish et al 2007), the parents used in mapping populations of rice have been screened for their sensitivity to high temperature (Jagadish et al 2007) for use in breeding of improved heat tolerance in rice. However, considerable further study needs to be conducted to determine the variation in acclimation to high temperatures and high temperature tolerance in crop species.…”
Section: Impact Of Climate Change On Cropping Systemsmentioning
confidence: 99%
“…They also found pollen viability is sensitive to high temperatures with lowland rice genotypes being more vulnerable than upland ones. Jagadish et al [6] found both upland and lowland rice spikelet sterility induced with less than 1 hr of exposure to an air temperature of at least 33.7°C and higher, based on a controlled environment experiment. Lowland indica rice exhibited a reduction in spikelet fertility by 7% per°C increase of temperature above 29.6°C whereas spikelet fertility was reduced by 2.4% per°C increase above 33°C for upland japonica rice [6].…”
Section: Introductionmentioning
confidence: 99%
“…Jagadish et al [6] found both upland and lowland rice spikelet sterility induced with less than 1 hr of exposure to an air temperature of at least 33.7°C and higher, based on a controlled environment experiment. Lowland indica rice exhibited a reduction in spikelet fertility by 7% per°C increase of temperature above 29.6°C whereas spikelet fertility was reduced by 2.4% per°C increase above 33°C for upland japonica rice [6]. In japonica rice, the critical temperatures to induce 50% sterility were estimated to be about from 36.5 to 38.5°C [2].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of heat stress on rice yield depends on the genotype, the growth stage at which heat stress is received and the period of the stress (Liao et al 2014;Poli et al 2013;Zhou et al 2012;Ye et al 2011;Jagadish et al 2010a;Prasad et al 2006;Morita et al 2005). In general, when rice plants are exposed to temperature greater than 35°C for more than one hour at anthesis, it results in increased sterility (Jagadish et al 2007). High temperature stress caused abnormal anther dehiscence and poor pollen germination which in turn increased spikelet sterility (Matsui and Omasa 2002;Jagadish et al 2010a).…”
Section: Introductionmentioning
confidence: 99%